Chemical crowd control agents. (March 2016) - Menezes, Ritesh G; Hussain, Syed Ather; Rameez, Mansoor Ali Merchant; Kharoshah, Magdy A; Madadin, Mohammed; Anwar, Naureen; Senthilkumaran, Subramanian
Chemical crowd control agents are also referred to as riot control agents and are mainly used by civil authorities and government agencies to curtail civil disobedience gatherings or processions by large crowds. Common riot control agents used to disperse large numbers of individuals into smaller, less destructive, and more easily controllable numbers include chloroacetophenone, chlorobenzylidenemalononitrile, dibenzoxazepine, diphenylaminearsine, and oleoresin capsicum. In this paper, we discuss the emergency medical care needed by sufferers of acute chemical agent contamination and raise important issues concerning toxicology, safety and health.